PENGARUH KARAKTERISTIK PEKERJAAN, DUKUNGAN ATASAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS KETAHANAN PANGAN DAN PETERNAKAN PROVINSI SUMATERA UTARA - Yuliana Dewi (Universitas Islam Sumatera Utara, 2020)
How does the effect of job characteristics on employee performance in the Department of Food and Animal Husbandry of North Sumatra Province. How does boss support influence employee performance at the Department of Food and Animal Husbandry of North Sumatra Province. How does the influence of organizational commitment on employee performance in the Department of Food and Animal Husbandry of North Sumatra Province. How the influence of job characteristics, boss support and organizational commitment to the performance of employees in the Department of Food and Animal Husbandry of North Sumatra Province.The purpose of this research was to determine the effect of job characteristics on employee performance in the Department of Food and Animal Husbandry of North Sumatra Province. To determine the effect of boss support on the performance of employees in the Department of Food and Animal Husbandry of North Sumatra Province. To determine the effect of job characteristics, boss support and organizational commitment to the performance of employees in the Department of Food and Animal Husbandry of North Sumatra Provinc.The sample in this research amounted to 51 employees. Data analysis technique used in this research is multiple linear regression analysis.The results of this research partially explain the job characteristics there is a significant influence on employee performance. Partial support from boss has no significant effect on employee performance. Partial organizational commitment does not have a significant effect on employee performance. Job characteristics, boss support and organizational commitment simultaneously have a significant effect on employee performance in working at the Department of Food and Animal Husbandry of North Sumatra Province.